Pengelolaan Modal Sosial dalam Meningkatkan Kinerja Usaha BUMDes Tulufali Desa Nggodimeda Kecamatan Rote Tengah Kabupaten Rote Ndao - Marthen Lona (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to examine the management of social capital in improving the business performance of Tulufali Village-Owned Enterprises (BUMDes) in Nggodimeda Village, Rote Tengah District, Rote Ndao Regency. Social capital is considered a key factor in strengthening BUMDes businesses and improving the welfare of village communities. The research method used is descriptive qualitative with a case study approach, through in-depth interviews and participatory observation. The research results show that effective management of social capital, including social networks, trust and social norms, plays an important role in improving the business performance of BUMDes Tulufali. These findings provide an important contribution to the development of a social capital management model that can be applied in the context of local economic development in rural areas, especially BUMDes Tulufali in running and maintaining the continuity of its business in the future.